2023
DOI: 10.1097/acm.0000000000005061
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between USMLE Step 2 Clinical Knowledge Scores and Residency Performance: A Systematic Review and Meta-Analysis

Abstract: Purpose With the change in Step 1 score reporting, Step 2 Clinical Knowledge (CK) may become a pivotal factor in resident selection. This systematic review and meta-analysis seeks to synthesize existing observational studies that assess the relationship between Step 2 CK scores and measures of resident performance. Method The authors searched MEDLINE, Web of Science, and Scopus databases using terms related to Step 2 CK in 2021. Two researchers identified studies investigating the association between Step 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Noteworthy studies have demonstrated the presence of racial biases associated with USMLE board scores and AΩA status. 3,8,10,11,[16][17][18] Our primary aim encompassed the intentional mitigation of established racial biases during the initial phases of the selection process, with the intention of preempting their impact on our interview evaluations, which we contend hold greater importance in shaping our rank list. It is pertinent to acknowledge that our application process remains an ongoing and dynamic endeavor, characterized by a holistic approach that continues to evolve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy studies have demonstrated the presence of racial biases associated with USMLE board scores and AΩA status. 3,8,10,11,[16][17][18] Our primary aim encompassed the intentional mitigation of established racial biases during the initial phases of the selection process, with the intention of preempting their impact on our interview evaluations, which we contend hold greater importance in shaping our rank list. It is pertinent to acknowledge that our application process remains an ongoing and dynamic endeavor, characterized by a holistic approach that continues to evolve.…”
Section: Discussionmentioning
confidence: 99%
“…Although Shirkhodaie et al showed that Step 2 CK scores have a statistically significant moderate positive association with future examination scores, they found a statistically significant weak positive correlation with overall, subjective measures of resident performance. 8 However, Udawatta et al demonstrated no significant correlation between USMLE Step 2 CK scores and ABNS written examination scores. 9 AΩA status has been shown to not correlate positively with faculty evaluations, in-training examinations, board examinations, chief resident selection, or research productivity across a variety of specialties.…”
mentioning
confidence: 97%
“…7 However, even with USMLE Step 2 exams, the correlation between scores and residency performance remains uncertain. 8…”
Section: Introductionmentioning
confidence: 99%
“…7 However, even with USMLE Step 2 exams, the correlation between scores and residency performance remains uncertain. 8 To address these concerns, the Federation of State Medical Boards (FSMB) and the NBME partnered with the American Medical Association, the Association of American Medical Colleges, and the Educational Commission for Foreign Medical Graduates to convene a summit, the Invitational Conference on USMLE Scoring. Following discussions at the summit and feedback solicited on a website, the FSMB and NBME made the decision to transition to P/F scoring.…”
Section: Introductionmentioning
confidence: 99%